IMPACT OF INTEGRATED REPORTING DISCLOSURE ON ACCOUNTING-BASED PERFORMANCE OF ASIAN LISTED COMPANIES - Qian G.; Sapingi R.; Husin N.M. (Universiti Malaysia Sarawak, 2024)
This study aims to examine the relationship between the quality of integrated reporting (IR) disclosure and firm performance in Asia listed companies. An integrated report score based on eight content elements taken from the IIRC framework was used to assess the quality of the IR disclosures of 90 Asian companies in 2019. Firm performance is evaluated using accounting-based measures such as return on assets (ROA) and return on equity (ROE). This study used a positivist research approach, the results show that the quality of IR disclosure of listed companies in Asia is sufficient. The study found a significant positive relationship between IR disclosure quality and ROA & ROE. It shows that the higher the quality of IR disclosure, the better the economic benefits of the company. The main practical implications of this study focus on calling for improved quality of IR issued by listed companies in Asia, as it provides evidence for a higher degree of financial performance achieved through high-quality disclosure of IR. 2023, Universiti Malaysia Sarawak. All rights reserved.